Design and Analysis of Expert System to Measure Software Quality using EAOMT - Yahya, Zainab Hussain (Arab Journal for Sciences and Research Publishing, 2017)
In this research a Computer Aided Software Engineering Tool (Case Tool) Has been designed which is called (Expert Analysis For Metrics Tool EAFMT) which is used within design activity , this tool implements one of the famous Artificial Intelligence Techniques which is Expert Systems , which automatically evaluate and enhance system quality. This tool Measures Software Quality within design Activity , Its work depends on the analysis of Class diagrams (A Class Diagram is one of the Unified Modeling Language (UML) Diagrams) , which is done by construction of a parser that extract the necessary information to find design metrics , then each metric is evaluated alone within the Expert System. This tool Aims reducing the resources used and the huge time spent in checking the programs related to design, and Also ensures that the produced system has high quality as the costumer and user expected. This tool performance was tested by applying the hole Automated Teller Machine diagram for mobile devices ( which is built using Object Oriented Programming ) to it , And it succeeded in analyzing and evaluating diagram Quality based on Expert Systems.